2005
DOI: 10.1152/ajprenal.00003.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of EGF receptor in a model of salt-sensitive hypertension

Abstract: Because previous studies have shown that activation of the epidermal growth factor receptor (EGFR) produces a mitogenic stimulus in VSMC and the EGFR participates integrally in the vasoconstrictor responses of renal arterioles, the present study analyzed the expression of EGFR in these animals. Compared with Sprague-Dawley (SD) rats, renal cortical expression of EGFR was increased in both prehypertensive and hypertensive S rats. Immunohistochemistry using a polyclonal antibody to EGFR demonstrated that EGFR ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
2
19
0
1
Order By: Relevance
“…Histopathological manifestations of chronic renal injury in Dahl SS rats include glomerular hypertrophy, glomerulosclerosis, interstitial inflammation, interstitial fibrosis, tubular atrophy, and the fibromuscular thickening of interstitial arteries (63,86,94,97,106). In accord with several studies in SHRs (6,44,62,91), we demonstrate that FO prevents the development of chronic glomerular, tubulointerstitial, and vascular alterations in SS ϩ HSD rats.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Histopathological manifestations of chronic renal injury in Dahl SS rats include glomerular hypertrophy, glomerulosclerosis, interstitial inflammation, interstitial fibrosis, tubular atrophy, and the fibromuscular thickening of interstitial arteries (63,86,94,97,106). In accord with several studies in SHRs (6,44,62,91), we demonstrate that FO prevents the development of chronic glomerular, tubulointerstitial, and vascular alterations in SS ϩ HSD rats.…”
Section: Discussionsupporting
confidence: 88%
“…By quantitative analysis of trichrome-and Sirius red-stained slides, we demonstrate that FO significantly reduces interstitial fibrosis. Arteriopathic alterations, characterized by vascular smooth muscle hyperplasia and luminal constriction, are characteristic histopathological features of renovascular hypertension in Dahl SS rats and in SHRs (88,97,101,106). We found that FO reduced vascular fibromuscular hyperplasia in SS ϩ HSD rats, as evidenced by an increased lumen-to-wall thickness ratio of interlobular-sized arteries and arterioles.…”
Section: Discussionmentioning
confidence: 57%
“…17 Furthermore, renal cortical expression of the EGF receptor is increased in both prehypertensive and hypertensive SS rats compared with Sprague-Dawley rats. 39 As measured in this study with ELISA assay, EGF concentration in the kidney cortex of SS rats fed a HS diet was significantly lower compared with SS rats on a LS diet or SS.13 BN rats on both diets ( Figure 6). …”
Section: Egf Deficiency In the Renal Cortex Contributes To Saltsensitsupporting
confidence: 49%
“…Also, the renal VSM expression/ activity of EGFR is increased in Dahl-SS rats before the onset and in established HTN. EGFR mediates the fibrogenic and vasoconstricting actions of ANG II and ET-1, and inhibition of EGFR attenuates the HTN caused by ANG II and the renal vascular fibrosis in L-NAME-induced HTN (47,190).…”
Section: Renal Vsm Dysfunction In Htnmentioning
confidence: 99%